CD19+CD11c+T-bet+ B cells in myasthenia gravis: a potential biomarker - Lu, Yaru; Shen, Huimin; Wang, Yiye; Ma, Kai; Sun, Ruihua; Zhao, Ying; Li, Yaqiong; Ma, Qian; Zhang, Jiewen (Frontiers in Neurology, 2025)
BackgroundMyasthenia gravis (MG), an autoimmune disorder characterized by B cell-driven autoantibody production, exhibits heterogeneous B cell subsets dysregulation and incompletely defined signaling mechanisms.MethodsA cohort of 20 naïve MG patients positive for anti-acetylcholine receptor (AChR) antibodies and 15 healthy controls was analyzed. Peripheral blood mononuclear cells underwent proteomic profiling, flow cytometry (age-associated B cells (ABCs), plasma cells, T follicular helper cells, and regulatory B cells), and western blot validation of nuclear factor kappa-B (NF-κB)/cellular reticuloendotheliosis oncogene homolog (c-Rel) expression. Clinical severity was assessed using quantitative MG (QMG) scores. Statistical analyses included differential protein expression, pathway enrichment, and receiver operating characteristic (ROC) curve evaluation.ResultsProteomics revealed significant activation of the B cell receptor and NF-κB/c-Rel signaling pathways in MG patients, validated by upregulated NF-κB/c-Rel expression (p < 0.01). Flow cytometry demonstrated elevated ABCs (CD19+CD11c+T-bet+), plasma cells, and T follicular helper cells, alongside reduced regulatory B cells in MG (p < 0.001). The proportion of ABCs correlated positively with QMG scores (r = 0.5015, p = 0.024) but not with AChR antibody titers, suggesting antibody-independent mechanisms. ROC analysis identified moderate diagnostic utility of ABCs for moderate-to-severe MG (QMG scores ≥ 6; area under the curve = 0.68, 95% confidence intervals: 0.42–0.94).ConclusionThis study establishes ABCs and NF-κB/c-Rel signaling as central contributors to AChR-MG immunopathology. Therefore, ABCs may serve as complementary biomarkers for clinical stratification.